MODERN DIDACTIC TERMS IN THE CONTENT OF LATVIAN LANGUAGE AND LITERATURE STUDIES - Vulāne, Anna; Stikute, Elita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article is devoted to a pending matter in the Latvian linguistics and methodology of language and literature – the formation of the system of terminology. The 90-ies of the 20th century when Latvia gained its national independence brought changes not only in the political and economic life but also in the terminology because new realities, which appeared in life, needed new names. Essential transformation in education brought along changes in the nomination system of the specific realities in the sphere. By establishing broader contacts with the pedagogical information field of the Western countries, translating scientific articles one comes in touch with specific concepts of the sphere for which there are no matching nominative units in Latvian and, judging by publications, in most cases equivalent terms are successfully formed. Unfortunately, this is not true of all innovatons, which, due to lack of time, amount of work or other reasons, in most cases are not submitted to language experts or the terminology commission for approval. The research provides analysis of several terms used in the methodology of the Latvian language and literature, as well as other subjects, yet are contraversial from the viewpoint of terminology and the quality of the Latvian language. The research presents the analysis of the semantic structure of active teaching methods and methodological approaches in language and literature in the context of the Latvian language world view with the aim to encourage teachers, lecturers of institutions of higher education, specialists in pedagogy and didactics and other people concerned to consider whether one or another name (which can hardly be referred to as ‘term’) fits into the education process.